Comparison of 3-D Raytracing and Finite Frequency Tomography - Sandy K Suhardja; Yosua Hotmaruli Lumban Gaol; Agus Abdullah; Andri Dian Nugraha; Z. Zulfakriza (Himpunan Ahli Geofisika Indonesia (HAGI), 2019)
We performed 3-D seismic tomography using teleseismic arrival time at Southwest Mexico. The Mexican subduction zone results from successive fragmentation events that affected the ancient Farallon plate as various segments of the East Pacific rise approached the paleo-trench off western North America. The complexity in this region is related to two subducting oceanic plates, the Rivera and Cocos plates, that have different ages, compositions, convergence velocities and subduction dip angles. In this study, we compared the 3-D raytracing tomography model with finite frequency tomography model. Final models show the differences in amplitude and pattern between the raytracing and finite frequency. 3D raytracing models produced sharper images of fast velocity structures in the mantle. The deeper slabs are more coherent and show less broadening with depth than using 1D finite frequency kernels. However, although the finite frequency and 3-D ray tracing models show some differences in amplitude and pattern, the overall agreement of the models supports the interpretation of Yang et al. (2009) that slab rollback is occurring in South Western Mexico. One possible different interpretation between the raytracing and finite frequency theory results concerns the deep structure of the Rivera slab. The finite frequency models show that the Rivera slab is clearly observable at a depth of about 300km but fades away at greater depths. However, the 3-D ray tracing model shows a clear fast velocity band down to a depth of 400 km and thus our model does not support a slab tear of the Rivera plate above 400 km depth